Concentration of some trace element in water, sediment and Phragmites australis (Cav.), in Al-Diwaniya river - M. Hussein , Haider (University of Thi-Qar Journal of Science, 2019)
The current study was conducted to determine concentration of some trace elements in, water, sediments, and plant Phragmites australis(Cav.), in Al-Diwaniya river. Samples were collected monthly for water, sediments, plant. from May(summer) 2013 up to April(spring) 2014 from three sites from Al-Diwaniya river. The current study included determine some physical and chemical parameters such as air and water temperature, pH, , Salinity, Dissolved oxygen, Total Organic Carbon ; and soil texture, as well as measured of some trace elements (cadmium, copper, nickel, lead and zinc) in water (dissolved and particulate), and in sediment, and so in biotic component included plant P. australis.The results showed that the air and water temperature ranged between (16.40-39.55) ˚c ;( 11.42-30.57) ˚c respectively. The study also demonstrated that the pH values were neutral tend to light alkaline and ranged between (7.34-8.10), according to the values of salinity ranged between (0.773-0.954)‰ the water of the river was classified as Oligohaline, , and also showed dissolved oxygen as its value ranged between (401.2-7.979) mg/l , The values of total organic carbon in sediments ranged between (0.440- 1.045)%, While the sediment texture was sandy-silt in the first site , and sandy-clay in the both two and three sites of Al-Diwaniya river .Results of concentration of trace elements were determined Al- Diwaniya river ecosystem for all (cadmium, copper, nickel, lead and zinc) that the concentration of dissolved trace elements ranged between (.0....0-.0..1.0),( .0..14 -.0..40),( .0..10-.0..24), (.0...40- .0..4.. ),( .0.120 - .0.4.4 ) mg/l., whereas in particulate phase ranged for between (0.29-1.49), (3.46-13.04),( 12.51-20.99),( 1.08- 4.67(,(65.54-127.51 ) µg/g dry weight. and in sediments ranged between (0.53-1.96),( 23.93- 49.65),( 136.85- 166.09),( 4.14-5.92),( 126.69-176.64) µg/g dry weight respectively. In the Descending sequence in concentrations of all trace elements in abiotic components was as follow: sediments> particulate phase > dissolved phase. concentrations of trace elements (cadmium, copper, nickel, lead and zinc) in producers of Al-Diwaniya river ranged in plant P. australis from (0.07-0.20),( 5.93-16.21),( 8.67-46.87 ),( 0.89-2.93),( 26.60-103.78) µg/g dry weight respectively.